Platelet interaction with bacterial toxins and secreted products. (June 2015) - Shannon, Oonagh
Abstract Bacteria that enter the bloodstream will encounter components of the cellular and soluble immune response. Platelets contribute to this response and have emerged as an important target for bacterial pathogens. Bacteria produce diverse extracellular proteins and toxins that have been reported to modulate platelet function. These interactions can result in complete or incomplete platelet activation or inhibition of platelet activation, depending on the bacteria and bacterial product. The nature of the platelet response may be highly relevant to disease pathogenesis.